2010
DOI: 10.3109/01913121003770701
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis: Ultrastructure of Interstitial Cells in Myenteric Plexus

Abstract: Interstitial cells of Cajal (ICC) are key regulatory cells in the gut. In the colon of patients with severe ulcerative colitis (UC), myenteric ICC had myoid ultrastructural features and were in close contact with nerve terminals. In all patients as opposed to controls, some ICC profiles showed degenerative changes, such as lipid droplets and irregular vacuoles. Nerve terminals often appeared swollen and empty. Glial cells, muscle cells, and fibroblast-like cells (FLC) showed no alterations. FLC enclosed macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 69 publications
3
18
3
Order By: Relevance
“…Other cellular features, including mitochondrial ultrastructure, were generally undisturbed. These changes were similar to the changes in ICC that we had previously found in patients resected for severe UC in which the most pronounced changes were seen in ICC-SMP as compared with myenteric ICC (Rumessen 1996;Rumessen et al 2010). We did not perform quantitative electron microscopy, and the small sample size precluded conclusions being made with regard to segmental variations or the influence of disease severity, disease duration or types of medication.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Other cellular features, including mitochondrial ultrastructure, were generally undisturbed. These changes were similar to the changes in ICC that we had previously found in patients resected for severe UC in which the most pronounced changes were seen in ICC-SMP as compared with myenteric ICC (Rumessen 1996;Rumessen et al 2010). We did not perform quantitative electron microscopy, and the small sample size precluded conclusions being made with regard to segmental variations or the influence of disease severity, disease duration or types of medication.…”
Section: Discussionsupporting
confidence: 89%
“…The treatment protocol of control and patient tissue was similar in all studies. The tissue was processed for transmission electron microscopy and studied as previously described (Rumessen 1994(Rumessen , 1996Rumessen et al 2009Rumessen et al , 2010. Immediately after resection, pieces of colon were immersed in a modified Karnovsky fixative of 8%+8% or 12%+12% glutaraldehyde (Taab, Berkshire, UK) and paraformaldehyde (Merck, Darmstadt, Germany) or a modified Zamboni fixative of 4%+4% glutaraldehyde and paraformaldehyde with picric acid (Merck) added from a saturated solution to give a final concentration of 0.18% in 0.1 M phosphate buffer (Merck) at pH 7.3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…full-thickness) specimens that represent an optimal substrate to document possible neuromuscular colonic alterations. 34 Electron microscopic studies, for instance, revealed that in patients with severe UC, ultra-structural abnormalities of the pacemaker cells -the so-called interstitial cells of Cajal (ICC) -are present in the sub-muscular pacemaker region 35 and the myenteric area 36 of the colon. Subsequent immunohistochemical investigations documented that, compared with controls, colonic specimens of UC patients express cyclooxygenase 2 in the myenteric neurons, suggesting that this expression, through an increased prostaglandin synthesis at this site, may contribute to the dysmotilty seen in this condition.…”
Section: Colonic Motor Abnormalities In Uc: Studies On Full-thicknessmentioning
confidence: 99%
“…The structure and function of the ENS in functional and inflammatory disorders of the gastrointestinal (GI) tract has been described [10,11]. However, little is known about the structure of myenteric plexuses in patients with colorectal cancer (CRC).…”
Section: +mentioning
confidence: 99%